Patient burden and healthcare resource utilization of regimens for ovarian stimulation. Issue 3 (March 2022) - Crespi, Simone; Hu, X. Henry; Johnson, Brett; Griesinger, Georg; Ledger, William L.; Heisel, Olaf; Kolibianakis, E.M.
Highlights: Ovarian stimulation protocols may contribute to women's stress during IVF treatment The psychological impact was less with corifollitropin alfa than daily gonadotrophins The psychological impact of ovarian stimulation increases with treatment intensity ABSTRACT: Research question: Do women receiving corifollitropin alfa with a gonadotrophin-releasing hormone (GnRH) antagonist experience less emotional and/or physical exhaustion than women receiving standard of care gonadotrophin with daily administration of GnRH agonist or antagonist? Design: The CoRifollitropin EvAluation in PracTicE (CREATE) study was a prospective observational study of fertility clinics in 17 countries in Europe and the Asia-Pacific region. Women undergoing IVF were categorized by treatment. Group A received single-dose corifollitropin alfa plus a GnRH antagonist; group B received usual care daily gonadotrophin regimens with a GnRH agonist or antagonist; and group B1i received daily GnRH agonist injections. For the primary analysis, two items from the Controlled Ovarian Stimulation Impact questionnaire were used to assess the level of emotional and physical exhaustion associated with ovarian stimulation. Secondary end-points included the impact of ovarian stimulation-related healthcare resource use. Results: No statistical difference was found between the percentage of participants reporting emotional exhaustion in group A (11.6%) and B (13.1%) or the percentage reporting being 'often' or 'always' physically exhausted. More participants in group B1i (16.4%) reported being emotionally exhausted 'often' or 'always' during ovarian stimulation compared with group A (11.6%; P  = 0.026). Patient questionnaire scores for psychological impact were higher in group A compared with group B, indicating less negative impact (72.7 versus 70.9; P  = 0.004). Group A had fewer clinic visits, physician consultations, nurse contacts and transvaginal ultrasound scans (all P  < 0.001) than group B1. Conclusions: Treatment with corifollitropin alfa resulted in similar or numerically small differences in psychological impact and lower clinic service use compared with daily gonadotrophin regimens.